Consumer Insight of Wearable Devices for Rumah Kayu Inc. Business Strategy - Setiabudi, Ananda; Iskandar, Budi Permadi (The Indonesian Journal of Business Administration, 2015)
Abstract - Along with growth of wearable devices market and lack of applications functionality for the devices, Rumah Kayu Inc. used it as opportunity as the market is attractive. This research focused on, Rumah Kayu Inc. strategy formulation on wearable applications based on consumer needs that created from consumer insight and strategy entering and lead the market. Generated business strategy are market penetration, market development, and product development strategy, in order to have a competitive advantage on compete and lead within existing competitor and new entrants. These strategies also supported by implementation plan to guide the company achieving a sustainability in the market and recommendation of feasibility studies for future works. Â Keywords: Business strategy, Consumer Insight, Market Penetration, Market Development